1986
DOI: 10.1177/002224378602300206
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Multiple Request Strategies: A Synthesis of Research Results

Abstract: Foot in the door and door in the face have been cited frequently as effective strategies for gaining compliance with behavioral requests. However, research efforts to confirm these two phenomena have produced mixed results. After deriving predictions about how the favorability of available information influences compliance, the authors report a synthesis of research results for both paradigms. Combined effect sizes across research results for several moderating variables are compiled. Implications for theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
0
4

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 17 publications
6
73
0
4
Order By: Relevance
“…However, direct tests of the theory fail to support the self-presentation explanation (Abrahams & Bell, 1994). Fern, Monroe, and Avila (1986) introduced the availability hypothesis to explain DITF effects. The theory suggests favorable information presented to individuals before a compliance request will increase compliance.…”
Section: Theoretical Accounts Of Ditf Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, direct tests of the theory fail to support the self-presentation explanation (Abrahams & Bell, 1994). Fern, Monroe, and Avila (1986) introduced the availability hypothesis to explain DITF effects. The theory suggests favorable information presented to individuals before a compliance request will increase compliance.…”
Section: Theoretical Accounts Of Ditf Effectsmentioning
confidence: 99%
“…In the case of DITF, the authors suggested larger concessions as a proxy for the amount of favorable information available to message recipients. However, the authors' own meta-analysis (Fern et al, 1986) failed to provide evidence for this contention, and the theory has since been abandoned.…”
Section: Theoretical Accounts Of Ditf Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the first two offers for each debtor, subjects could enter into a repeating sequence of best-offers (overlined in the figures) that consisted entirely of high and medium offers. The overall pattern of state transitions used in the debtor STDs was derived from foot-in-the-door (FID) and door-in-the-face (DIF) phenomena observed in functioning environments (Cialdini, 1984;Fern et al, 1986). In FID, bargainers get their opponents to accede to a relatively low request and then move them up to levels that they could not have obtained on one request alone.…”
Section: Bargaining Taskmentioning
confidence: 99%
“…Existing evidence suggests that the FITD tactic is effective in producing enhanced compliance in many settings and in response to a wide range of requests (e.g., Beaman, Cole, Preston, Klentz, & Steblay, 1983;Beaman, Steblay, Preston, & Klentz, 1988;Burger, 1999;Fern, Monroe, & Avila, 1986).…”
mentioning
confidence: 99%